Rising Above Office Conflict: A Light-Hearted Guide for the Heavy-Hearted Employee - Fowler, Clare E (Rowman & Littlefield Publishers, 2023)
A light hearted guide offering step-by-step advice that empowers readers to understand and overcome the conflicts they face at work. Building on 20 years of workplace disputes, this book brings practical tools for resolving conflicts right into the employee’s hands. With a humorous and engaging approach, this book is a guide for everyone frustrated at work. The characters described are relatable, and the suggestions are described in a simple, easy-to-adopt plan. Why is conflict in every workplace? Because there are so many different types of people with different needs, and no idea how to work together. Clare Fowler provides a hilarious overview of 2 wonderful personalities and 18 difficult ones (Micromanager, Chatty Cathy, The Hulk, Inappropriate Ivan, etc.) and gives you strategies for dealing with them. Explaining common processes for resolving conflict, she provides a quick and ready guide for any employee hoping to manage conflict, rise above the fray, and move forward successfully with everyone they work with. She offers suggestions for preventing conflict from reoccurring. Worksheets and solutions explorers will help you to find an easy plan for rising above your office conflict.